TEACHING INTEGRATING PROJECT AS AN ACTIVE THEATER PRACTICE IN A RURAL SCHOOL: ADAPTATION OF THE PLAY “O AUTO DA BARCA DO INFERNO” - da Silva Carvalho, Vitor; Serrão Ferreira Silva, Dilma; Lima de Souza, Alcinete; Maria dos Santos Lima, Lúcia (Revista Gênero e Interdisciplinaridade, 2024)
The application of an integrated project of language teaching in the new high school languages, led the authors of this work to develop an experience report that could combine the four components of the Language area - Portuguese Language and their literatures, English, art and Physical Education - with students of the São Felipe Annex School in the community of Cipoal in the municipality of Santarém. The work was developed in the 3 first year classes of that school in 2022, was based on the adaptation of the play of the Portuguese playwright Gil Vicente. The preparation lasted 2 and a half months from the beginning of the project, to rehearsals to the presentation. The evaluation process came from the observation of the students working in the theatrical / team of the scenario and selection of these for a night presentation to the community, with the evaluation of 1 to 40 points in each of the fields of knowledge, depending on their performance, besides Evaluation through PIE-LGG, having reference to authors such as Susan Holder, Gilian, Lazar, Domiguez, Granero, it was observed that integrating projects came to implement knowledge in contextualized practice for a development of linguistic skills, being the students the protagonists.